1988
DOI: 10.1099/00207713-38-2-173
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia seriolae sp. nov. Causing Nocardiosis of Cultured Fish

Abstract: were studied to establish their taxonomic status. Well-developed fragmenting vegetative mycelium was observed. The chemotype was type IVA containing rneso-diaminopimelic acid, arabinose, and galactose. The predominant isoprenoid quinone was MK-8(H4), and mycolic acids were present. These morphological and chemical properties are characteristic of the genus Nocurdiu. The physiological and biochemical characteristics were most similar to those of Nocurdiu usteroides; however, these organisms were different in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 32 publications
8
57
0
1
Order By: Relevance
“…Nocardia brasiliensis and Nocardia transvalensis are the main causal agents of actinomycete mycetoma (McNeil & Brown, 1994 ;McNeil et al, 1992), and the predominant agents of nocardiosis are Nocardia asteroides, Nocardia farcinica and Nocardia nova (Schaal & Lee, 1992 ;Wallace et al, 1991). Nocardia seriolae (Kudo et al, 1988) and Nocardia salmonicida (Isik et al, 1999) . are fish pathogens, whereas Nocardia crassostreae is the causal agent of nocardiosis in Pacific oysters (Friedman et al, 1998).…”
mentioning
confidence: 99%
“…Nocardia brasiliensis and Nocardia transvalensis are the main causal agents of actinomycete mycetoma (McNeil & Brown, 1994 ;McNeil et al, 1992), and the predominant agents of nocardiosis are Nocardia asteroides, Nocardia farcinica and Nocardia nova (Schaal & Lee, 1992 ;Wallace et al, 1991). Nocardia seriolae (Kudo et al, 1988) and Nocardia salmonicida (Isik et al, 1999) . are fish pathogens, whereas Nocardia crassostreae is the causal agent of nocardiosis in Pacific oysters (Friedman et al, 1998).…”
mentioning
confidence: 99%
“…Chemotaxonomy. Freeze-dried biomass of strain JCM 4826' (50mg) was degraded by acid methanolysis and hexane extracts examined for mycolic acids by TLC as described by Minnikin et al (1975Minnikin et al ( , 1980. Menaquinone was analysed using HPLC as described previously (Chun & Goodfellow, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Strain JCM 4826T, a fish pathogen isolated from blueblack salmon (Oncorhynchus nerka), was assigned to the genus Streptomyces as Streptomyces salmonicida (Rucker, 1949) but was transferred to the genus Nocardia as Nocardia salmonicida when wholeorganism hydrolysates of the strain were found to contain meso-diaminopimelic acid, arabinose and galactose (Pridham & Lyons, 1969 ;Pridham, 1970). This reclassification was subsequently underpinned by additional chemotaxonomic and morphological data (Goodfellow, 1971 ;Alderson et al, 1985;Kudo et 1988) and the organism was shown to be most closely related to Nocardia asteroides on the basis of the results from DNA : DNA relatedness (Mordarski et al, 1977;Kudo et al, 1988) and numerical phenetic (Orchard & Goodfellow, 1980) studies. ' Nocardia salmonicida' JCM 4826T also fell outwith the Streptomyces clusters in the numerical phenetic survey of Williams et al (1983).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen sources are not utilized. Kinoshita et al (2001), Kudo et al (1988), Maldonado et al (2000), Yassin et al (2001), Wang et al (2001) …”
Section: Description Of Nocardia Araoensis Sp Novmentioning
confidence: 99%